2013
DOI: 10.1186/1471-2377-13-179
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the Frontal Assessment Battery is sensitive to frontal lobe damage in stroke patients

Abstract: BackgroundThe Frontal Assessment Battery (FAB) is a brief battery of six neuropsychological tasks designed to assess frontal lobe function at bedside [Neurology 55:1621-1626, 2000]. The six FAB tasks explore cognitive and behavioral domains that are thought to be under the control of the frontal lobes, most notably conceptualization and abstract reasoning, lexical verbal fluency and mental flexibility, motor programming and executive control of action, self-regulation and resistance to interference, inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 70 publications
8
33
0
3
Order By: Relevance
“…Several studies have investigated this issue [22,23,55]; however, only a few studies have discussed WMHs and FAB [56]. In the present study, we found a strong association between TFAB performance and white matter changes within frontal and lateral periventricular regions and subcortical deep brain nuclei in the patients with both MCI-V and MCI-A.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Several studies have investigated this issue [22,23,55]; however, only a few studies have discussed WMHs and FAB [56]. In the present study, we found a strong association between TFAB performance and white matter changes within frontal and lateral periventricular regions and subcortical deep brain nuclei in the patients with both MCI-V and MCI-A.…”
Section: Discussionsupporting
confidence: 69%
“…It has been widely applied in studies on various target groups [17,18,19,20,21]. Researchers have discovered that neural substrates related to performances on the FAB include both cortical and subcortical areas, such as the middle frontal gyrus, inferior frontal, insula [22], callosomarginal, and precentral regions [23]. Previous studies have also shown that the FAB is useful in differentiating AD from subcortical VaD [24].…”
Section: Introductionmentioning
confidence: 99%
“…The FAB provides a useful screening instrument for executive dysfunction as shown in several clinical investigations, including studies on Parkinson's disease, Alzheimer's disease, or stroke 20, 43, 44. Brain imaging studies revealed positive correlations of decreased FAB scores indicating executive dysfunction and reductions of brain tissue perfusion located to the left middle frontal gyrus and the right superior frontal gyrus in patients with MCI, Alzheimer's disease, and frontotemporal lobe dementias 45, 46, 47.…”
Section: Discussionmentioning
confidence: 99%
“…БЛД включала визначення кон-цептуалізації, швидкості мовлення, динамічного праксису, просту та складну реакцію вибору та дослідження хватальних рефлексів. Якщо пацієнт набирав 18-16 балів, це відповідало нормальним когнітивним функціям, 15-12 балів -свідчило про помірну лобну дисфункцію за відсутності де-менції, а 11 балів та нижче -про деменцію лобно-го типу [11][12][13].…”
Section: матеріали та методиunclassified